Analysis Of Existing Mechanisms And Methods For Training Cybersecurity Specialists - PhD, Dotsent Nishanov I.I; Tursunov T.M (Genius Journals, 2025)
Cybersecurity specialists play an important role in combating risks and threats. With the development of the Internet and technologies, risks such as cyberattacks, data theft, and illegal access to systems are increasing. To combat these threats, it is necessary to train specialists. There is a shortage of qualified specialists in the field of cybersecurity, therefore, it is important to improve education systems and train them based on new methods. The knowledge and skills of specialists must be regularly updated, taking into account rapidly changing technologies. The introduction of innovative approaches and modern methods in ensuring cybersecurity helps to improve the skills of specialists
Keywords: Cybersecurity; risks; threats